1995
DOI: 10.1021/ie00038a054
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Water by N-Halamine Biocidal Polymers

Abstract: Two novel polymers have been tested in a filter application for biocidal efficacy for flowing aqueous solutions of microorganisms. A laboratory water pump was employed in the experiments to provide contact times on the order of 1-2 s/mL. The two polymers are N-chlorinated and N-brominated derivatives of a polystyrene hydantoin. The variables of pH, temperature, flow rate, and dilution with inert sand have been examined. The N-bromamine polymer (Poly-IB) was generally more effective than the N-chloramine polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 7 publications
(13 reference statements)
1
71
0
Order By: Relevance
“…However, some biocidal activity is retained in the presence of the quenching agent which suggests some biocidal effect depends on the action of the halogenated polymer itself and proceeds through contact between bacteria and polymer particles. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This dual mechanism of killing (contact + release of halogen species) is currently under investigation and will be reported in due course. In addition to these two expected modes of action there is another possibility: killing the bacteria by changing the nature of the environment around the bacterial cells by exchanging the halogen between the halogenated polymer and proteins in medium.…”
Section: -Iodinated Polymer (7)mentioning
confidence: 99%
“…However, some biocidal activity is retained in the presence of the quenching agent which suggests some biocidal effect depends on the action of the halogenated polymer itself and proceeds through contact between bacteria and polymer particles. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This dual mechanism of killing (contact + release of halogen species) is currently under investigation and will be reported in due course. In addition to these two expected modes of action there is another possibility: killing the bacteria by changing the nature of the environment around the bacterial cells by exchanging the halogen between the halogenated polymer and proteins in medium.…”
Section: -Iodinated Polymer (7)mentioning
confidence: 99%
“…It was observed that the filters inactivated numerous species of bacteria, fungi, and even rotavirus in only seconds of contact time in flowing water. [11][12][13][14][15] Also, it was observed that the columns did not leach out decomposition products into the water, 14 and that the free chlorine and bromine concentrations leached into the flowing water were less than 0.1 mg/L and less than 2.0 mg/L, respectively. Furthermore, once the halogen supply was exhausted through various loss processes, it could be replenished on the polymers by simply exposing them to flowing aqueous free halogen (e.g., sodium hypochlorite bleach for the chlorinated derivative).…”
Section: Introductionmentioning
confidence: 98%
“…These include cellulose, 5 , 6 nylon, 6 , 7 PET, 6 , 8 Kraton rubber, 9 various surface coatings, 10 and the N-halogenated poly(styrene) hydantoins. [11][12][13][14][15] The latter polymers are granular solids which are insoluble in water and which were packed into glass columns which functioned as a cartridge filters. It was observed that the filters inactivated numerous species of bacteria, fungi, and even rotavirus in only seconds of contact time in flowing water.…”
Section: Introductionmentioning
confidence: 99%
“…The N-Halamine biocidal polymers described in the literature are water-insoluble; therefore they can be used safely in sterilizing drinking water and many other applications, such as disinfecting water supplies, swimming pools, hot-tubs, industrial water systems, and other applications where a sanitized water supply is required [15][16][17][18][19][20][21][22][23][24][25]. N-Halamine biocidal polymers have been prepared previously by introducing five or six membered heterocyclic rings containing amide or imide functional groups to be halogenated (Scheme 1, d) [15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%